ADSORPTION STUDIES ON THE REMOVAL OF Fe (II) ION FROM AQUATIC ENVIRONMENT USING NANO POROUS CARBON - Sivakumar, R; Arivoli, S (IJRDO-Journal of Applied Science, 2017)
The present study is on adsorption of Fe(II) ions by Activated Syringodium IsoetifoliumLeaves Nano Carbon. It uses batch adsorption techniques. The influence of contact time, initialconcentration, dosage of adsorbent and effect of solution pH were investigated. The equilibriumadsorption data were correlated with Langmuir, Freundlich, Temkin, Dubinin-Radushkevich,Hurkins-Jura, Halsay, Radlich-Peterson, Jovanovic and BET isotherm models. The isothermstudies of RL values showed that the adsorption process was favorable. Thermodynamicparameters such as ∆H0, ∆S0and ∆G0 were evaluated. The data indicate that, the adsorption wasspontaneous and is an endothermic nature. Adsorption kinetics was tested with pseudo- secondorder,Elovich model and intra – particle diffusion models. Kinetic studies indicate an adsorptionpseudo-second-order reaction. This study shows that intra-particles played a major role in theadsorption of Fe(II) ions mechanism. The Activated Syringodium Isoetifolium Leaves NanoCarbon has high adsorption capacity and adsorption rate for the removal of Fe(II) ions fromaqueous solution